Dendrological key and species characterization of the subfamilies Mimosoideae and Caesalpinioideae, Tocantins, Brazil - Bezerra, Samila; Ribeiro, Adriana Santos Neves; Oliveira, Patrick Peres; Gomes, Yusuky de Sousa; Felicio, Jhessyka Yasminni Lobo Ferreira Fermandes; Da Silva, Renata Carvalho; De Souza, Priscila Bezerra (OBSERVATÓRIO DE LA ECONOMÍA LATINOAMERICANA, 2023)
Much of the vegetation in the State of Tocantins belongs to the Cerrado domain, widely known for hosting several species and forest families, among which the Fabaceae family stands out. However, misguided practices, incipient public policies, and few studies on the subject culminate in the loss of species found in the Cerrado of Tocantins. The present work aimed to elaborate a dichotomous key through dendrological characters. This study was carried out at the Federal University of Tocantins, Gurupi campus, which consisted of expeditions, and a collection of branches of tree species of the Fabaceae family in order to describe the vegetative characters. Seven species belonging to the Fabaceae family were analyzed, four from the Mimosoideae subfamily and three from the Caesalpinioideae subfamily. Characteristics such as bark color, extrafloral nectary, hairiness, and leaf classification allowed us to notice the differences between each sampled species. It can be inferred that the dendrological key of forest species of the Fabaceae family is fundamental for forest inventories and management plans of botanical species of the Cerrado Domain.